Comparative Analysis of Altman, Springate, and Zmijewski Models in Predicting the Bankruptcy of Retail Companies in Indonesia and Singapore - M. Muzanni; Indah Yuliana (TIJAB (The International Journal of Applied Business), 2021)
This study aims to determine whether there is a difference in the prediction results between the Altman, Springate, and Zmijewski models and the most accurate prediction model for predicting the bankruptcy of retail companies in Indonesia and Singapore. This research is descriptive quantitative. The sampling method used was purposive sampling with 15 Indonesian retail companies and 15 Singapore retail companies. This study used descriptive analysis, normality test, and One Way ANOVA test using an SPSS program. The results showed that: 1) There are significant differences between the Altman model, Springate model, and Zmijewski model in Indonesian retail companies. 2) There is a significant difference between the Altman model, Springate model, and Zmijewski model in the Singapore retail companies. 3) The most accurate model in predicting the bankruptcy of Indonesian retail companies is the Zmijewski model. 4) The most accurate model in predicting the bankruptcy of Singapore retail companies is the Altman model.